Complete genome sequence of a Hobi-like virus isolated from a Nelore cow with gastroenteric disease in the state of São Paulo, Brazil - Cortez, Adriana; Araújo, João Pessoa [UNESP]; Flores, Eduardo Furtado; Ribeiro, Márcio Garcia [UNESP]; Megid, Jane [UNESP]; Paes, Antonio Carlos [UNESP]; de Oliveira Filho, José Paes [UNESP]; Ullmann, Leila Sabrina [UNESP]; Malossi, Camila Dantas [UNESP]; Heinemann, Marcos Bryan (American Society for Microbiology, 2017)
The Hobi-like virus presents antigenic and molecular differences in relation to bovine virus diarrhea virus 1 and 2. The description of the complete genome of the Hobi-like virus SV757/15, isolated from a Nelore cow with gastroenteric disease in Brazil, will help in understanding the evolution and diversity of pestiviruses.